1993
DOI: 10.1163/22941932-90000570
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Callus at the Graft Interface in Sitka Spruce

Abstract: The early stages of graft union formation in Sitka spruce [Picea sitchensis (Bong.) Carr] have been examined using light microscopy in order to determine the origin of callus between the scion and rootstock. All living, undamaged cells exposed to the environment by the process of stern preparation for grafting have been found to be capable of producing callus. The first cells to respond in this way, within two days of grafting, were the epithelial cells of severed resin canals and ray parenchyma exposed where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The effect of cambium has been reported in different graft survival studies [26,36,52]. It has been reported that the meristematic activity of the cambium between the scion and the rootstock is an important factor in the successful establishment of the graft [16,17]. In the present study, the size of the surface area of the scions and the rootstock plants showed a similarity of 97%; however, the cambium of the scions is irregularly shaped, in contrast to the almost circular shape of the cambium of the rootstock plants (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of cambium has been reported in different graft survival studies [26,36,52]. It has been reported that the meristematic activity of the cambium between the scion and the rootstock is an important factor in the successful establishment of the graft [16,17]. In the present study, the size of the surface area of the scions and the rootstock plants showed a similarity of 97%; however, the cambium of the scions is irregularly shaped, in contrast to the almost circular shape of the cambium of the rootstock plants (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Carr. [16], and in the genus Rhododendron L. [17]. Three important stages of graft development are recognized in this process: callus formation, cambial differentiation, and cambial continuity (vascular tissue formation) [18].…”
Section: Introductionmentioning
confidence: 99%